Option Pricing Models: A Study of the Black-Scholes-Merton Model - Xue Kexuan (SHS Web of Conferences)
Financial Derivatives refer to financial instruments whose value depends on or is derived from other underlying assets such as stocks, bonds, commodities, exchange rates, and interest rates Examples include futures and options. This paper first introduces the early theories of option pricing. It then focuses on the Black-Scholes model, discussing the academic modifications and expansions made to this model due to its theoretical assumptions not aligning with reality. These adjustments aim to explore more efficient and practical methods for calculating option prices.